Human Tau Isoforms and Proteolysis for Production of Toxic Tau Fragments in Neurodegeneration - Boyarko, Ben; Hook, Vivian (Frontiers in Neuroscience, 2021)
The human tau protein is implicated in a wide range of neurodegenerative ‘tauopathy’ diseases, consisting of Alzheimer’s disease (AD) and frontotemporal lobar degeneration which includes progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), Pick’s disease (PiD), and FTDP-Mapt (frontotemporal dementia with parkinsonism caused by MAPT mutations). Tau gene transcripts in the human brain undergo alternative splicing to yield 6 different tau protein isoforms that are expressed in different ratios in neurodegeneration which result in tau pathology of paired-helical filaments (PHFs) and neurofibrillary tangles (NFTs), with detrimental microtuble destabilization. Protease-mediated tau truncation is an important post-translational modification (PTM) which drives neurodegeneration in a tau fragment-dependent manner. While numerous tau fragments have been identified, knowledge of the proteolytic steps that convert each parent tau isoform into specific truncated tau fragments has not yet been fully defined. An improved understanding of the relationships between tau isoforms and their proteolytic processing to generate neurotoxic tau fragments is important to the field. This review evaluates tau isoform expression patterns including PTMs and mutations that influence proteolysis of tau to generate toxic fragments that drive cognitive deficits in AD and other tauopathy models. This assessment identifies the gap in the field on understanding the details of proteolytic steps used to convert each tau isoform into fragments. Knowledge of the processing mechanisms of tau isoforms can lead to new protease targeted drug strategies to prevent the formation of toxic tau fragments in tauopathy neurodegenerative diseases.